Students’ Learning Attitudes toward CDIO- Based Business Administration Course Design: An Investigation from two Universities in Central Vietnam - Tran , Ngoc Hai; Pham, Kien The; Bui, Hung Van; Duong, Thanh-Thanh Thi; Tran, Nghia Dai (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to investigate students’ learning attitutes toward the application of “Conceive-Design-Implement-Operate” (CDIO) approach in two Departments of Economics-Business Administration Faculty in two universities in Central Vietnam. The study aimed to investigate students’ creative thinking ability, problem-solving ability and their attitudes toward this ‘learning by doing’ and ‘outcome-based learning’ method. The sample was composed of 339 students from two departments of those two universities who were chosen to complete a 32-item questionnaire on a Likert scale to measure their learning attitudes toward the CDIO-based Business Administration courses. The results showed that students are more engaged and motivated in the courses, and they learn how to integrate feedback from their peers. Overall, all the students have positive attitudes toward the CDIO-based program and they are willing to take more relevant courses in the future.